A study on the construction of evaluative system of Smart City based on entropy‐weighted matter‐element model method. (4th December 2018) - Yong, Xiang; Yan, Cui; Weiyao,; Qiang, Xu
Summary: Since our country has started to build the pilot project of a smart city in 2013, its effect has already appeared tentatively promoted by policies. However, its evaluation system is not yet mature. Therefore, this technical paper first considered the construction of evaluation index system according to the concept and construction situation of Smart City, adopted the five‐year statistics of Sichuan Province as empirical data, and this paper applied modeling calculation to draw the objective state of current Smart City construction. It also included the construction of evaluation index system with the introduction of a matter‐element extension method and entropy method to assign the weights, discussed the changes in the maximum relational degree of the six rule hierarchy indicators, and analyzed the key index that influences its development in the soft urban environment and information service to point out the direction for the next phase of the development.